Sosialisasi Pentingnya Digital Marketing Sebagai Salah Satu Strategi dalam Mengembangkan Usaha Mikro Kecil dan Menengah (UMKM) di Kelurahan Turi Kota Blitar - Gideon Setyo Budiwitjaksono; Amalia Rizky Chairinnisa; Dina Indah Nurcahyani; Diva Delia Rossa Nicolas; Talitha Pandya (Institut Nalanda, 2023)
: The digital era gave rise to new habits for MSMEs. It’s by using digital technology for business development. This community service activities through socialization aim to increase knowledge and skills in implementing digital marketing to develop the potential of MSMEs in Turi. This research method was carried out online and offline through four sessions, namely, conducting surveys, socialization, collecting responses through questionnaires, and assisting the implementation of digital marketing to MSMEs in Turi. So, KKN-T students carry out a program in the form of socialization and assistance in implementing digital marketing to develop MSMEs. The outreach activities have resulted in a good enthusiasm and response from the MSME participants. There are three MSMEs that want to be assisted in implementing digital marketing, there is Emping Jagung, Frozen Food Mas Fian, and Omah Kelor. Assistance is done by creating website, social media accounts, e-commerce, and content bank. Thus, it is hoped that holding this activity can develop more potential of MSMEs in Turi, Blitar City